Plume moths (Lepidoptera: Pterophoridae) of Ethiopia. Part 3 - Ustjuzhanin, Peter Ya (Ecologica Montenegrina)
The article gives a faunal overview on Pterophoridae of Ethiopian considering all the literature data and new findings. The plume moths fauna of Ethiopia currently includes 59 species, 6 of which are reported for the first time (marked with *). For the latter, data on collected specimens and photos of adults are used.